Analisis Perkembangan Wisata Halal dan Dampaknya terhadap Ekonomi Korea Selatan pada Tahun 2019-2021 - Putri, Tantry Hardiansal (Journal of International and Local Studies, 2025)
The development of halal tourism in South Korea has been a focal point for the government and relevant institutions since the early 2010s. South Korea took strategic measures to enhance accessibility and services for Muslim tourists visiting the country. Since the launch of the "Muslim Friendly Korea" program in 2014, various initiatives have been implemented to strengthen halal tourism infrastructure, including the provision of halal food facilities, the promotion of halal tourism through multiple media, and the development of Muslim-friendly facilities such as mosques and places of worship. These efforts have been instrumental in attracting Muslim tourists to South Korea and boosting the economic impact of the tourism sector. This study employs a qualitative research method, utilizing secondary data analysis that includes official reports, literature studies, and financial statistics related to halal tourism and South Korea's economic growth from 2019 to 2022. Based on the analysis of GDP (Gross Domestic Product) data, South Korea has successfully maintained its economic growth in the tourism sector through the development of halal tourism.